Peran Karyawan Untuk Meningkatkan Loyalitas Konsumen - Iriani Ismail; Mila Puspitasari; Fitri Isnaini Fausia; Moh Miko Indrawan (Journal of Management and Creative Business, 2023)
This research aims to determine the influence of employee roles and service quality, both partially and simultaneously, on consumer satisfaction at Cafe Joker Telang. This type of research is descriptive research with a quantitative approach. The population in this study were employees, consumers and Cafe Joker owners. The sample in this study was 4 respondents obtained using nonprobability sampling techniques. Data collection techniques use interviews, documentation and observation. The data analysis technique used is multiple linear regression analysis with SPSS version 23.0 tools. The conclusion of this research is that the quality and discipline of employees formed by the Cafe Owner, influences consumer satisfaction at Cafe Joker.